Reading Norms and Social Roles on Film “KTP” - Davinta Alifia (Universitas Pendidikan Indonesia, 2021)
As an Indonesian citizen, there must be norms that must be considered in daily activities as social beings. Norms act as values of decency that are embraced by the whole society. In addition, the community also has their respective social roles in a group. Many short films picture the reality of people's lives, one of which is the film 'KTP'. Based on this, the author wants to describe the norms and social roles contained in the film 'KTP'. The author uses a qualitative descriptive method by focusing on the analysis of Charles Sanders Peirce, namely by paying attention to the icon (icon), index (index), and symbol (symbol). The observations obtained are that in the 15 minutes 33-second KTP film, there are norms and social roles that are conveyed, including greetings, procedures for visiting and receiving guests, deliberation to reach consensus, as well as an overview of the social roles prevailing in society. This film clearly shows a portrait of the reality of the social life of the Indonesian people through a dynamic approach.